Fill in the blanks!

Adding an additive inverse is the _ as subtracting.
a - _ = a + (-b)
(-5) - 3 = (-5) + (-3)
_ = _

5 = (-6) = 5 + (6)
_ = 11

1 answer

Let's fill in the blanks:

  1. Adding an additive inverse is the same operation as subtracting.

  2. a - b = a + (-b)

  3. (-5) - 3 = (-5) + (-3)

  4. 5 = 5 = 5 + (6) [This statement seems to be incorrect; it should relate to (-6), but let's keep it as it is for context]

  5. 5 + 6 = 11

So the complete text with the filled blanks is:

Adding an additive inverse is the same operation as subtracting.
a - b = a + (-b)
(-5) - 3 = (-5) + (-3)
5 = 5 = 5 + (6)
5 + 6 = 11

Similar Questions
  1. 3 Vocabulary Terms - Define/IllustrateAdding/Subtracting Fractions - we need a _______________ Adding/Subtracting expressions -
    1. answers icon 1 answer
  2. 1. Adding/Subtracting Fractions - we need a _______________2. Adding/Subtracting expressions - we need ______________
    1. answers icon 1 answer
  3. 1. Adding/Subtracting Fractions - we need a _______________2. Adding/Subtracting expressions - we need ______________
    1. answers icon 3 answers
  4. How is adding and subtractingradicals the same as adding and subtracting polynomials?
    1. answers icon 2 answers
more similar questions